2021
DOI: 10.3390/min11030301
|View full text |Cite
|
Sign up to set email alerts
|

Geological Controls on Enrichment of Rare Earth Elements and Yttrium (REY) in Late Permian Coals and Non-Coal Rocks in the Xian’an Coalfield, Guangxi Province

Abstract: The highly elevated concentrations of the rare earth elements and yttrium (REY), U, Mo, Se, and Pb in late Permian coals in some coalfields in Guangxi Province, South China, have been widely investigated; however, the mode of occurrence and enrichment mechanism of these critical elements are still under debate. This study investigates the mineralogical and geochemical compositions of coals and non-coal rocks from the Xian’an Coalfield in Guangxi Province to discuss the geological factors influencing the distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Some previous studies have indicated that the Yunkai Upland located to the east of the Heshan, Yishan, Fusui, and Xian'an Coalfields (Figure 1B) is the dominant sediment source region providing felsic detrital materials into the late Permian coal-bearing basins in Guangxi Province, China [5,6]. However, a few studies have demonstrated that some detrital materials within the late Permian coal-bearing strata in Guangxi Province are probably derived from the basaltic materials from the Kangdian Upland [25], the eroded materials from the felsic igneous rocks at the top of the Kangdian Upland [26,27].…”
Section: The Nature Of Detrital Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some previous studies have indicated that the Yunkai Upland located to the east of the Heshan, Yishan, Fusui, and Xian'an Coalfields (Figure 1B) is the dominant sediment source region providing felsic detrital materials into the late Permian coal-bearing basins in Guangxi Province, China [5,6]. However, a few studies have demonstrated that some detrital materials within the late Permian coal-bearing strata in Guangxi Province are probably derived from the basaltic materials from the Kangdian Upland [25], the eroded materials from the felsic igneous rocks at the top of the Kangdian Upland [26,27].…”
Section: The Nature Of Detrital Materialsmentioning
confidence: 99%
“…Uranium, Mo, V, As, and Se Uranium, Mo, and V are highly enriched in layer A and layer B and their contents are comparable to the U-Mo-V-rich coals intercalated within carbonate successions [3,5,8,46]. The highly elevated U content is commonly accompanied by Mo and V in the Heshan coals [1][2][3], Fusui coals [5], Yishan coals [13] (anomaly), and Shanglin coals [6], which were deposited in isolated carbonate platform environments. In the previous study, the highly enriched concentrations of U, Mo, and V are primarily governed by the infiltration of syngenetic or early diagenetic low-temperature hydrothermal fluids rather than the detrital materials from the sediment-source region and marine influence as confirmed by the following evidence:…”
Section: Mode Of Occurrence Of Elementsmentioning
confidence: 99%
See 3 more Smart Citations